Persistent Left Superior Vena Cava: Implications of Surgical Management - Robin Boyer; Ramanjeet Sidhu MD; Aslan Ghandforoush MD; Theingi Win MD; Arash Heidari MD (SAGE Publishing, 2019)
Persistent left superior vena cava is the most common congenital anomaly of thoracic venous return, which results when the left anterior cardinal vein fails to regress. A 41-year-old African American male with a history of an unspecified childhood cardiac murmur presented to the emergency department with congestive heart failure exacerbation revealing an incidental finding of a persistent left superior vena cava. Ultimately, he required implantable cardioverter defibrillator placement and cardiac transplantation assessment. In the setting of advanced device placement or cardiac transplantation, a persistent left superior vena cava warrants several important clinical considerations at a center capable of addressing the possibility of a right-sided approach and transplantation irregularities.